Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Toko Sembako Di Desa Tluwah - Umi Nur Kholifah Umi; Umi Nur Kholifah; Lola Indra Mukti; Wasis Wijayanto (CV. ITTC INDONESIA, 2025)
This research aims to analyze effective marketing strategies in increasing sales of Mrs. Nasri's basic food shop in Tluwah village. This research uses a qualitative descriptive approach by collecting data through observation, interviews and document analysis. This analysis shows that the use of marketing strategies based on social relations, improving the quality of customer service, and utilizing promotions via local social media can be significant in increasing sales. Apart from that, maintaining complete product availability and affordable prices is an important thing which is a key factor in maintaining customer loyalty. The combination of these marketing strategies is considered very effective in attracting new customers and increasing sales at Nasri's grocery store. Thus, a marketing strategy that focuses on market segmentation, strategy (product, price, promotion and service) is a strategic step that can be implemented to increase the competitiveness and sales of basic food stores in the Tluwah village environment.